2017
DOI: 10.1073/pnas.1704393114
|View full text |Cite
|
Sign up to set email alerts
|

An epigenetic switch repressing Tet1 in gonadotropes activates the reproductive axis

Abstract: The TET enzymes catalyze conversion of 5-methyl cytosine (5mC) to 5-hydroxymethyl cytosine (5hmC) and play important roles during development. TET1 has been particularly well-studied in pluripotent stem cells, but -KO mice are viable, and the most marked defect is abnormal ovarian follicle development, resulting in impaired fertility. We hypothesized that TET1 might play a role in the central control of reproduction by regulating expression of the gonadotropin hormones, which are responsible for follicle devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 35 publications
(55 reference statements)
1
64
0
Order By: Relevance
“…In the first study to describe Tet1 S , it was reported to be the only transcript expressed past early developmental stages (Zhang et al, 2016). Yet, others have recently provided evidence that in some adult tissues and/or cell types, Tet1 FL and Tet1 S are co-expressed (Good et al, 2017;Yosefzon et al, 2017). We found that while Tet1 S is the predominantly expressed isoform in the brain, Tet1 FL is also actively transcribed.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In the first study to describe Tet1 S , it was reported to be the only transcript expressed past early developmental stages (Zhang et al, 2016). Yet, others have recently provided evidence that in some adult tissues and/or cell types, Tet1 FL and Tet1 S are co-expressed (Good et al, 2017;Yosefzon et al, 2017). We found that while Tet1 S is the predominantly expressed isoform in the brain, Tet1 FL is also actively transcribed.…”
Section: Discussionsupporting
confidence: 48%
“…A potential explanation for some of these inconsistences comes from a recent report that the Tet1 gene undergoes an isoform switch from the full-length, canonical transcript (hereafter Tet1 FL ) in embryonic stem cells to a shorter, truncated variant (hereafter Tet1 S ) exclusive to somatic tissues (Zhang et al, 2016). In addition, evidence suggests that in some tissues both transcripts might be co-expressed (Good et al, 2017;Yosefzon et al, 2017). Whether this is the case in the adult brain, and if so, what functions these Tet1 isoforms might serve, has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Highly expressed in ESCs, PGCs, and inner cell mass of blastocyst, TET1 protein has been proven to be mainly responsible for the initial oxidation of 5-mC to 5-hmC, and to establish the paradoxically dual distinct epigenetic patterns in transcriptional activation and repression in accordance with life processes of growth and development. Alternative splicing mechanism leads to several TET1 isoforms, including the full-length canonical and the short transcripts [69][70][71][72][73]. TET1 expression is regulated by very complicated factors including the reprogramming factors such as Oct3/4, Nanog, and Myc [68,70] in early embryos, ESCs and PGCs [69], the transcription factors in the differentiated cells, and STAT3/STAT5 in acute myeloid leukemia (AML) [74].…”
Section: Tet1 and Regulation Of Its Target Gene Expressionmentioning
confidence: 99%
“…Differentiation with according increase in the expression of the luteinizing hormone gene (Lhb). The short isoform of TET1 with deletion of the N-terminal CXXC-domain binds the H3K27me2/3 enriched region located at the upstream promoter of the Lhb gene, downregulating its expression and leading to differentiation deficiency [73].…”
Section: Tet1 and Regulation Of Its Target Gene Expressionmentioning
confidence: 99%
“…RNA was isolated using Trizol, DNase I digested and cDNA synthesized using the High Capacity cDNA Reverse Transcription Kit (Thermo Fisher Scientific, Waltham, MA, USA), and real-time quantitative PCR (qPCR) was conducted using the Perfecta SYBR Green FastMix (Quantabio, Beverly, MA, USA) both as previously reported (45); the primers listed in Table 1 were used for the analyses. Amplicon levels were normalized to levels of Rplp0.…”
Section: Rna Extraction Real-time Pcr and Transcriptome Analysismentioning
confidence: 99%